Primary school teachers’ opinion on value education - Shah, Rajendra Kumar; Chand, Rita (Journal of Tikapur Multiple Campus, 2017)
In ancient times, Krishna financially helped his childhood friend Sudama. Now day's brothers are quarrelling for money and ready to kill each other. Eklavya gave his teacher Dronachrya his thumb happily. Nowadays, a student will not hesitate even for a second before cutting his teacher's thumb. These things prove that people were really good at heart in ancient time because they were taught moral values from the very beginning. That is where present students lag in. Delivery of the knowledge, attitude and skills related to values in schools is as essential as the emphasis on education itself in 21st century. Curriculum designers in every country ought to take values into account. Values rooted deep in the history of nations are of vital importance for the future of the societies. In order to avoid interruptions of transfer of values in children, inclusion of values in school curriculums is inevitable. The present study includes opinion and suggestions of 10 purposively selected primary school teachers of Kailali district on values education, contents of school textbooks, pedagogy they exploit, challenges and policies adopted by government. The whole study depends on interviews of 10 open ended questions. The present study concludes with recommendations on school curriculums and textbooks, pedagogical aspects and ways of tackling challenges in values education. Findings of the present study indicated that values education is urgently needed in Nepal. For this purpose, school education curriculum should be revised and contents related to values should be incorporated in the existing primary education curriculum to make it more relevant from the perspectives of value-based education.